Proposal for the restoration and architectural rehabilitation of the Polvorín de San Carlos in Cusco - Villa Carmona, Eyprol Danae (2022)
This thesis is the result of       an investigation based on historical and planimetric documents, which formulates through it a proposal for the restoration and architectural rehabilitation of the "Gunpowder warehouse of San Carlos in Cusco"; a building declared architectural heritage of the Nation that has been abandoned and forgotten over time, constituting a unique- representative reference of the typology of military architecture of the 18th century in Cusco. The general objective was to formulate a proposal for the restoration and architectural rehabilitation of the gunpowder warehouse of San Carlos for a new use of "cultural, public, flexible and safe space for the city of Cusco." It is concluded that the proposal for the restoration and rehabilitation of the gunpowder warehouse of San Carlos guarantees its preservation and the structural consolidation of heritage, promoting public, cultural and flexible spaces for Cusco, integrating the intervention into the urban landscape of the city.